Using Interactive Hybrid Online Labs for Rapid Prototyping of Digital Systems - Henke, Karsten; Tabunshchyk, Galina; Wuttke, Heinz-Dietrich; Vietzke, Tobias; Ostendorff, Steffen (International Journal of Online and Biomedical Engineering (iJOE), 2014)
The Ilmenau Interactive Hybrid Online Lab offers several fields of application. In this article an enhancement of the existing Online Lab will be described to provide additional functionalities for a Web-based rapid prototyping of digital systems as well as the Web-based verification of such systems. For this new operation mode of the online lab a special rapid-prototyping board for digital systems was developed to fulfill the design tasks of digital systems. All the components of the rapid prototyping board will be described in detail. The implemented online lab infrastructure allows to interconnect online labs and to exchange remote lab experiments among different universities worldwide.